2022
DOI: 10.1088/1361-6579/ac89cb
|View full text |Cite
|
Sign up to set email alerts
|

Label noise and self-learning label correction in cardiac abnormalities classification

Abstract: Objective. Learning to classify cardiac abnormalities requires large and high-quality labeled datasets, which is a challenge in medical applications. Small datasets from various sources are often aggregated to meet this requirement, resulting in a final dataset prone to label noise owing to inter- and intra-observer variability, and different expertise. It is well known that label noise can affect the performance and generalizability of the trained models. In this work, we explore the impact of label noise and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…A few shot learning approach using siamese convolutional networks (SCNN) [148] was recently proposed; this method achieved an accuracy of up to 95% on the publically available INCART 12-lead Arrhythmia dataset [149] . Vázquez et al adapted a self-learning multi-class label correction method to learn a multi-label classifier for ECG signals and evaluated the model using 5-fold cross-validation [150] . They successfully demonstrated that self-learning label correction can effectively address unknown label noise and improve classification accuracy even with the reduced number of ECG leads.…”
Section: Efficient Models For Ecg Cardiac Rhythm Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…A few shot learning approach using siamese convolutional networks (SCNN) [148] was recently proposed; this method achieved an accuracy of up to 95% on the publically available INCART 12-lead Arrhythmia dataset [149] . Vázquez et al adapted a self-learning multi-class label correction method to learn a multi-label classifier for ECG signals and evaluated the model using 5-fold cross-validation [150] . They successfully demonstrated that self-learning label correction can effectively address unknown label noise and improve classification accuracy even with the reduced number of ECG leads.…”
Section: Efficient Models For Ecg Cardiac Rhythm Classificationmentioning
confidence: 99%
“… [148] (2023) Siamese-CNN INCART 12-lead Arrhythmia dataset A few shot learning approach using siamese convolutional networks for Arrhythmia classification. Contrastive Loss was used for training the model which gave best performance, as the loss function [150] (2022) 1D-CNN PhysioNet/CinC 2021 A self-learning multi-class label correction method to learn a multi-label classifier in presence of noisy labels. …”
Section: Efficient Models For Ecg Cardiac Rhythm Classificationmentioning
confidence: 99%
“…A 1D-CNN similar to [16] was used for classification. The model takes the sEMG pattern of a single stride, consisting of the M. semitendinosus and the M. rectus femoris, as input and the predicted instruction as output.…”
Section: D Convolutional Neural Networkmentioning
confidence: 99%
“…This could have lowered the accuracy. To eliminate the effect of this label noise on the classifier, label correction during training could be applied [16].…”
Section: E Limitationsmentioning
confidence: 99%